1970
DOI: 10.3126/hren.v9i3.5579
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of VIA comparing with conventional pap smear in the detection of colposcopic biopsy proved CIN

Abstract: Introduction: Cervical cancer, the leading malignancy among Indian women is preventable and curable if detected at an early stage using proper screening tools. We conducted a study to assess the role of visual inspection with acetic acid as an alternative to pap smear and in screening program for cervical cancer in low resource settings. Methods: Two hundred and twenty five women in reproductive age group attending the Gynecology department at K.S Hegde Charitable Hospital were enrolled in the study. A Papanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…10 Vaidya had showed that low socio economic status had a definite role in development of dyskaryosis. 11 Duration of marriage and duration of exposure to sexual intercourse had a distinct role in genesis of cervical dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…10 Vaidya had showed that low socio economic status had a definite role in development of dyskaryosis. 11 Duration of marriage and duration of exposure to sexual intercourse had a distinct role in genesis of cervical dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…In the cross sectional study done in October 1995 to August 1997women attending 15 primary health center in Zimbabwe [8] to study the efficacy of VIA and cytology in the study group, the age group included was 25 to 55 years and the mean age was 33.25. In a study evaluating the efficacy of VIA with conventional pap smear by Divya Hedge et al [9], 56.6% belonged to the 41-50 year age group and 68.5% belonged to the lower middle age group.…”
Section: Characteristics Of the Study Groupmentioning
confidence: 99%
“…The common presenting symptom in women with dysplasia was also white discharge per vagina. In a study evaluating the efficacy of VIA with conventional pap smear by Divya Hedge et al [9], the major presenting complaint was menstrual irregularities in 40.8% women. 12.9% of women had complaints of white discharge per vagina.…”
Section: Characteristics Of the Study Groupmentioning
confidence: 99%
“…Papanicolaou smear is an un-invasive safe method that can be used to detect all grades of cervical intra epithelial neoplasia (CIN) (10). Sensitivity of Pap smear test ranges from 30%-87% and its specificity ranges from 86% to 100% (11).…”
Section: Introductionmentioning
confidence: 99%